2005
DOI: 10.1080/14660820510026162
|View full text |Cite
|
Sign up to set email alerts
|

Optimal methods to characterize the G93A mouse model of ALS

Abstract: In the present study, we used the SOD1 (G93A) mutant transgenic mice as a model of amyotrophic lateral sclerosis (ALS). This model is widely used as a laboratory tool to study experimental treatments in vivo for ALS to investigate new therapeutic strategies for this neurodegenerative disease. Such studies require the objective quantification of different parameters while mice develop the disease. We have applied a battery of different and specific tests: scoring of motor deficits by a trained observer, weighin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
85
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 11 publications
11
85
0
1
Order By: Relevance
“…Several studies using a modified hanging wire test found that SOD1-G93A and control mice perform similarly from 56 days of age until time-to-fall latencies of SOD1-G93A mice decrease significantly at 98 days of age (Weydt et al;Miana-Mena et al, 2005). In contrast, other studies revealed long-standing deficits apparent at earlier time-points.…”
Section: Fore-and Hindlimb Motor Deficitsmentioning
confidence: 76%
See 3 more Smart Citations
“…Several studies using a modified hanging wire test found that SOD1-G93A and control mice perform similarly from 56 days of age until time-to-fall latencies of SOD1-G93A mice decrease significantly at 98 days of age (Weydt et al;Miana-Mena et al, 2005). In contrast, other studies revealed long-standing deficits apparent at earlier time-points.…”
Section: Fore-and Hindlimb Motor Deficitsmentioning
confidence: 76%
“…Maximal force exerted by two hindlimb muscles, measured via tetanic contraction, was significantly reduced at 90 days of age in SOD1-G93A mice when compared to control mice (Sharp et al, 2005). Physiological indications of muscle denervation (positive sharp waves and spontaneous fibrillation potentials), were detected in SOD1-G93A mice at 84 days of age (Miana-Mena et al, 2005).…”
Section: Fore-and Hindlimb Motor Deficitsmentioning
confidence: 84%
See 2 more Smart Citations
“…The rotarod test was performed to evaluate motor coordination, strength and balance [30,31] in all the animals used in the study (Table 1). Mice were trained three times a week on the rod rotating at 14 rpm, and then tested from 8 to 16 weeks of age, with an arbitrary maximum time of maintenance in the rotating rod of 180 seconds.…”
Section: Locomotion Testsmentioning
confidence: 99%